An Analytical Modeling Approach for Performance Evaluation of Electrostatic Precipitator (ESP) - Shanti Faridah, Salleh; Afrasyab, Khan; Cirilo Nolasco, Hipolito; Lennevey, Kinidi; Dayang Siti Herdawati, Abang Hardin (Penerbit UTM Press Universiti Teknologi Malaysia, 2019)
A coal-fired flue gas contains high concentrations of fine particles which can pose a threat to the environment. In this study, an electrostatic precipitator is used to remove the fine particles of the flue gas from a 100MW coal fired power plant by using a model. A model has been presented to estimate the performance of the wet electrostatic precipitator (WEP) in terms of the number of plates, flow rates and velocity. The equations have been specified for the charging and charge on the single particle of some definite diameter. The effect of the measuring points for the calculation of the effective migration velocities and hence overall performance along with the re-entrainment and gas sneakage have been incorporated. Ranges for the above-mentioned parameters are well defined and it has been observed that after a certain range values across number of plates, velocities and flow rates there is no significant improvement in the performance of the WEP has been calculated.